Differences in intraoperative hemodynamics between spinal and general anesthesia in infants undergoing pyloromyotomy. Issue 7 (17th April 2017) - Ing, Caleb; Sun, Lena S.; Friend, Alexander F.; Kim, Minjae; Berman, Mitchell F.; Paganelli, William; Li, Guohua; Williams, Robert K.
Abstract: Background: Hypotension and bradycardia are known side effects of spinal anesthesia in pregnant women undergoing cesarean section and adults undergoing other surgical procedures. Whether children experience similar hemodynamic changes is unclear. Aims: The purpose of this study is to evaluate hemodynamic effects of spinal anesthesia compared to general anesthesia in a cohort of healthy infants. Methods: The University of Vermont Medical Center almost exclusively used spinal anesthesia for infant pyloromyotomy surgery between 2008 and 2013, while Columbia University Medical Center relied on general anesthesia. The primary outcome assessed was the percentage change in intraoperative heart rate and blood pressure (systolic [SBP] and mean [MAP] blood pressure) from baseline. Analysis was performed using t ‐tests for continuous variables, followed by linear regression to account for differences in demographic and clinical covariates. Results: The study sample consisted of 51 infants with spinal anesthesia at the University of Vermont and 52 infants with general anesthesia at Columbia University. The decrease from baseline for mean intraoperative SBP was −8.2 ± 16.8% for spinal anesthesia and −24.2 ± 17.2% for general anesthesia (difference between means: 16.2% [95% confidence interval (CI), 9.5–22.9]), while the decrease from baseline for mean intraoperative MAP was −16.3 ± 19.9% for spinal anesthesia and −24.6 ± 19.3% for general anesthesia (difference between means: 8.4% [95% CI, 0.8–16]). Spinal anesthesia patients also had smaller drops in minimum intraoperative MAP and SBP. These blood pressure differences persisted even after adjusting for covariates. No differences in heart rate were seen between spinal and general anesthesia. Discussion: Our findings show that spinal anesthesia performed in healthy infants undergoing pyloromyotomy results in reduced intraoperative blood pressure changes from baseline, significantly higher blood pressure readings, and no increased bradycardia compared to general anesthesia. Further research is needed to assess whether any clinical impact of these hemodynamic differences between spinal and general anesthesia exists. Abstract :